Regulating mobility through detention: Understanding the new geography of control and containment at the Southern European border - Campesi, Giuseppe (Theoretical criminology, 2024)
The aim of this article is to describe the evolution of immigration detention policies at the Southern European border. This will be done by presenting original data on the actual functioning of immigration detention in Italy in the wake of the so-called “refugee crisis”. By shedding light on these developments, the article reveals a notable convergence of first reception and return policies, which in turn is driving a transformation of the landscape of immigration detention leading to a proliferation of detention regimes and spaces of containment. Drawing on the literature on carceral geographies, this development is analyzed within the framework of Italy's distinct role in the geopolitics of EU border control policies. The article ultimately suggests that the immigration detention system has gradually been co-opted by the border control infrastructure, becoming part of a broader and intricate control assemblage whose essential function is the regulation of human mobility.